Investigation of Deposits in Urea-SCR After-Treatment Systems for Heavy-Duty Diesel Engines - Zhang, Jiyuan; Sun, Shaojun; Wang, Yibao; Tao, Jianzhong; Li, Guoxiang (Asian Journal of Chemistry, 2013)
To ensure SCR system normal application, one of the basic requirements is to avoid the deposition of urea droplets including crystallization in the exhaust stream. Design and calibration principles are the main causes of urea deposition. Unreasonable structure design, machining and installation can lead to urea crystallization phenomenon inside the bore of the nozzle, on the exhaust pipe wall and the front end surface of the catalyst because of the insufficient atomization and decomposition of urea droplets. In addition, unreasonable calibration strategy can also deteriorate this condition. The components of the urea deposits were tested and analyzed by thermogravimetry-FTIR technology indicating that the urea deposits are the urea and cyanuric acid. On this basis, the modified structure of integral nozzle mounting is provided to improve the design. The engine dynamometer test and the vehicle road test were conducted showing that the optimal design and calibration strategy can effectively avoid crystallization and sedimentation in the system.